Uwarunkowania sukcesu zawodowego w opinii kadry kierowniczej przedsiębiorstw z Dolnego Śląska - Kupczyk, Teresa (Conditions of vocational success in the opinion of managers of Lower Silesian enterprises, 2006)
Nowadays, work success has got a crucial impact on social status of an individual as well as the way one estimates himself and his life. A question why some people achieve success easier than the others and some are never successful is still a subject of discussion. Thus, what determines success? This problem appears particularly essential in the context of high competence requirements imposed on contemporary staff, including management as well as in the light of, existing in Poland, the highest unemployment rate in the European Union and OECD. The problem is much more difficult in our country, because an average Polish takes part in the educational practices two times less often than European Union citizens and four times less often than Scandinavians or Dutch and five times than British. The author discusses and displays a part of the study results concerning determinants of work success in the opinion of managers and specialists employed in business, education and administration. The paper also reveals opinions of the unemployed. The range of the diagnosis encompasses the determinants of success which are directly related to a respondent, i.e. psychological features, knowledge and skills. The author attempts to compare and detect the differences among top and middle management, specialists and the unemployed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 61-69